Engineered pathogens: the opportunities, risks and challenges. (1st June 2019) - Nelson, Cassidy
Abstract : Before modern times, only nature was capable of engineering pathogens. This ability was by no means unimpressive: evolution has repeatedly demonstrated a formidable capacity for producing a vast array of infectious agents. Pathogens such as Variola major and Yersinia pestis, which cause smallpox and plague respectively, wielded enough destructive power to shape parts of human history. However, recent advancements in biotechnology mean it is now possible to engineer new viruses and bacteria. Developments in the field of synthetic biology present many exciting opportunities, enabling better understanding of disease-causing agents and facilitating the creation of new medical therapeutics and diagnostics. However, with these breakthroughs comes the risk that some of the worst pathogens in history could be recreated without requiring access to natural sources. Furthermore, engineered microbes may surpass the destructive potential of their evolved counterparts by being designed to be deadlier or more transmissible. These enhanced agents could pose an unprecedented pandemic threat to the global community. Given the risks, it is essential that regulatory frameworks for potentially hazardous research reflect modern capabilities and address emerging biosecurity concerns.